The effectiveness of biofertilizer biofilm formulation in promoting the growth of Pak choi (Brassica rapa L.) plant - Rosariastuti Retno; Harir Addina; Hartati Sri; Irawan Evi; Nugraha Setya (E3S Web of Conferences, 2023)
One of the climate changes is the El Nino phenomenon, causing the soil to dry out, so it needs to be addressed because it will impact plant growth. Farmers use a lot of inorganic fertilizers (NPK), and in the long term, it can cause soil damage. One alternative treatment is to use organic fertilizers or biological fertilizers. Biofilm biofertilizer is a form of biological fertilizer. This study aims to determine the effect of dosing biofilm biofertilizer on the growth of Pak choi plants so that it can help reduce the use of inorganic fertilizers. This type of research was an experiment in a greenhouse using a completely randomized design (CRD) with six treatments, consisting of A (100% inorganic fertilizer), B (75% inorganic fertilizer and 25% biofilm biofertilizer), C (50% inorganic fertilizer and 50% biofertilizer biofilm), D (25% inorganic fertilizer and 75% biofertilizer biofilm), E (100% biofertilizer biofilm), and F (no inorganic fertilizer and no biofertilizer biofilm). Each treatment was repeated four times. Parameters used in this study included plant height, number of leaves, dry weight and wet weight, and leaf diameter. Data analysis used the ANOVA test with a 95% confidence level, followed by Duncan's Multiple Range Test (DMRT). The results showed that the combination of 25% biofertilizer biofilm treatment with 75% inorganic fertilizer gave the best results compared to the control and other treatments. The treatment of 25% Biofilm biofertilizer with 75% inorganic fertilizer was able to increase plant height by 21.175 cm or 74.24% higher than control, number of leaves by 17.25 strands or 65.62% higher than control, leaf width by 7.125 cm or 61.80% higher than control, wet weight by 28.083 g or 97.29% higher than control, and dry weight by 1.869 g or 95.88% higher than control so that this treatment can be an alternative to reduce the use of inorganic fertilizer.